2018
DOI: 10.1038/s41467-018-07639-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of peroxiredoxin-2 exacerbates eccentric contraction-induced force loss in dystrophin-deficient muscle

Abstract: Force loss in skeletal muscle exposed to eccentric contraction is often attributed to injury. We show that EDL muscles from dystrophin-deficient mdx mice recover 65% of lost force within 120 min of eccentric contraction and exhibit minimal force loss when the interval between contractions is increased from 3 to 30 min. A proteomic screen of mdx muscle identified an 80% reduction in the antioxidant peroxiredoxin-2, likely due to proteolytic degradation following hyperoxidation by NADPH Oxidase 2. Eccentric cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 86 publications
6
65
3
Order By: Relevance
“…Cytoplasmic β‐ and γ‐actins are required for normal skeletal muscle function . We have shown that gross overexpression of cytoplasmic β‐ or γ‐actin by transgenic methods can protect mdx EDL muscle from ECC‐induced force loss , by either blocking the production of force‐inhibiting reactive oxygen species (ROS), or preventing ROS from oxidizing proteins important for muscle contraction . Our data showing that the mdx Sol muscle endogenously expresses significantly greater cytoplasmic β‐ and γ‐actins than the EDL and PL support a new mechanism to explain Sol insensitivity to ECC.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Cytoplasmic β‐ and γ‐actins are required for normal skeletal muscle function . We have shown that gross overexpression of cytoplasmic β‐ or γ‐actin by transgenic methods can protect mdx EDL muscle from ECC‐induced force loss , by either blocking the production of force‐inhibiting reactive oxygen species (ROS), or preventing ROS from oxidizing proteins important for muscle contraction . Our data showing that the mdx Sol muscle endogenously expresses significantly greater cytoplasmic β‐ and γ‐actins than the EDL and PL support a new mechanism to explain Sol insensitivity to ECC.…”
Section: Discussionmentioning
confidence: 70%
“…In fact, the Sol muscle, which is the most protected against ECC‐induced force drop, has the highest specific isometric tetanic force as well as the highest ECC : ISO compared to an EDL or PL. We recently proposed that mdx EDL muscle has an adaptive “circuit breaker” that limits force production to prevent ECC‐induced muscle damage . Based on the results of this study, it could be hypothesized that the Sol muscle does not have the same circuit breaker, potentially due to different cytoplasmic actin expression, MHC composition, or utrophin content.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations